Isophya nagyi, a new phaneropterid bush-cricket (Orthoptera: Tettigonioidea) from the Eastern Carpathians (Caliman Mountains, North Romania) - Szövényi, Gergely; Puskás, Gellért; Orci, Kirill Márk (Zootaxa, 2012)
This study describes Isophya nagyi sp. n. from the Caliman Mountains (Eastern Carpathians, Romania). This species wasdiscovered on the basis of the special rhythmic pattern of its male calling song. Regarding morphology Isophya nagyi issimilar to the species of the Isophya camptoxypha species-group (I. ciucasi, I. sicula, I. posthumoidalis, I. camptoxypha),however the male stridulatory file contains more stridulatory pegs (105–130) compared to the other members of thespecies group (50–80 pegs). Calling males produce a long sequence of evenly repeated syllables (repetition rate variesbetween 60–80 syllables at 21–24o C), and most importantly syllables are composed of three characteristic impulse groupscontrary to songs of the other species where syllables are composed of two elements or the song consists of two syllabletypes. Besides the description of the basic morphological features and pair-forming acoustic signals of the new species, a calling song based key is given for the I. camptoxypha species group.